A Four Slot Dual Feed and Dual Band Reconfigurable Antenna for Fixed Satellite Service Applications - Apparao, T. Venkata Suri; Karunakar, G. (International Journal of Electrical and Computer Engineering Systems, 2023)
A dual feed and dual-band reconfigurable antenna is designed, analyzed, and prototyped in this work for fixed satellite service communication applications. The designed model occupies the compact dimension of 24X21X1.2 mm on FR4 substrate and provides an input impedance of 50 ohms at both ports. The proposed model offers additional circular polarization characteristics at both the resonating bands. The PIN diode-based switching conditions, and the frequency reconfigurability analysis in both simulation and measurement are almost match. The combination of dual-band resonance, frequency reconfigurable nature, and compact dimension makes this model an attractive candidate in the specified field with considerable gain (8.5 dB) and efficiency (80%).